Pengaruh Pembiayaan Syariah terhadap Pertumbuhan UMKM di Indonesia - Bastian Ahmadan; Agung Laksono; Reni Ria Armayani Hasibuan (STIKes Ibnu Sina Ajibarang, 2025)
This research intends to assess the influence of sharia reform on the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on key sectors that underpin the national economy. This article employs quantitative methods and secondary data acquired via digital literature research to offer the most recent findings from many sources, including OJK publications, Bank Indonesia, and certified scientific journals. The study's results demonstrate that sharia-compliant principles, including mudharabah, musyarakah, and murabahah, substantially enhance the development, prosperity, and strength of MSMEs. Mudharabah, musyarakah, or murabahah substantially enhance the development, prosperity, and strength of MSMEs. This research provides significant insights for the advancement of equitable and sustainable finance within the Indonesian Islamic economic framework.